Comparison of Tolerance Related Proteomic Profiles of Two Drought Tolerant Tomato Mutants Improved by Gamma Radiation - ÇELİK, ÖZGE; AYAN, ALP; MERİÇ, SİNAN; ATAK, ÇİMEN (Elsevier B.V., 2021)
Lycopersicon esculentum L., also known as tomato, is an important industrial plant due to its products which worth billions of dollars annually, besides its nutritional value and health benefits. In this study, we investigated the two-dimensional protein expression profiles in drought tolerant mutant plants derived from industrial 5MX12956 tomato variety by Cs-137 gamma radiation source induced mutations. Drought tolerance of mutants were evaluated and confirmed by in vivo and in vitro methods. Eleven drought responsive protein spots were identified by two-dimensional electrophoresis and MALDI-TOF-MS. Identified proteins which presented differential expression under drought conditions were clustered under six distinct groups based on their cellular functions. These clusters are ATP and carbohydrate metabolism, mRNA processing and protein phosphorylation, oxidation reduction and stress response, signaling and supporting cytoskeleton. Our results contributed proteomic data to drought tolerance of our tomato mutants which were originated from drought susceptible 5MX12956 variety. They may also facilitate basis for future investigations into the genetic and physiological aspects of this tolerance. © 2021 Elsevier B.V.
Keywords: Lycopersicon Esculentum L. Drought Tolerance; Mutation Breeding; Proteomics